A model protocol evaluating the introduction of genetic assessment for women with a family history of breast cancer. Issue 3 (1st March 2000) - Gray, Jonathon; Brain, Kate; Norman, Paul; Anglim, Cathy; France, Liz; Barton, Garry; Branston, Lucy; Parsons, Evelyn; Clarke, Angus; Sampson, Julian; Roberts, Elizabeth; Newcombe, Robert; et al.
Abstract : Randomised controlled trials allow comparisons to be made between different models of service delivery, but have not been used in the field of clinical genetics. With the advent of clinical governance, the evidence provided by such trials will be increasingly important in informing and shaping clinical genetics practice. The TRACE project (Trial of genetic assessment in breast cancer) is a randomised controlled trial of genetic assessment for women who are at increased risk of breast cancer because of their family history. The absence of cancer genetics service provision in Wales before this study gave a window of opportunity in which this important trial could be conducted. The present paper describes how TRACE will provide crucial evidence regarding the psychosocial as well as resource implications of adding individualised genetic assessment, genetic counselling, and (where appropriate) gene testing to typical advice and surveillance from a hospital breast clinic. In addition, it is anticipated that TRACE will represent a model for future trials of service delivery in the increasing number of complex genetic disorders where evidence on the economic implications of screening and management is currently limited.